Triple Therapy with Garlic, Silymarin and Curcumin in Non-Alcoholic Fatty Liver Disease: A Randomized, Placebo-Controlled Clinical Trial - Zahra Ataee; Maryam Vahabzadeh; Seyedeh Shabnam Mazloumi Kiapey; Hamid Reza Rahimi; Hooman Mosanan Mozaffari; Maliheh Ziaee * (Lorestan University of Medical Sciences, 2022)
Background and Aim: Non-alcoholic fatty liver disease (NAFLD) is the most common liver disease in the world. We aimed to evaluate the effect of a mixture of garlic, silymarin, and curcumin on hepatic parameters and overall improvement of NAFLD. Materials and Methods: Individuals between 18 and 70 years of age with altered liver enzymes and confirmed pattern of fatty liver in their hepatic ultrasound were entered into this randomized, triple-blind, placebo-controlled trial and assigned to two groups. They received either capsules containing curcumin, silymarin and garlic or an identical placebo. After 3 months, the patients were re-evaluated for laboratory tests, clinical evaluation, and liver fibroscan. Data were analyzed in consistent with the intention-to-treat approach. Results: After randomization and blinding, 50 individuals entered this study. The mean age of the participants was 42.51 ± 11.13 (mean± SD) years of old, and 80% of the participants were men. After triple therapy, no significant differences were observed in laboratory tests between the two groups, except for the triglyceride level (188.86 ± 90.66 vs. 146.23 ± 70.38, p-value=0.04). However, hepatic fibroscans were noticeably ameliorated in the treatment group compared to the control (p-value <0.001). Conclusion: We observed no significant amelioration in the majority of biochemical indices of the patients, but patterns of NAFLD in fibroscans were considerably improved. Although we cannot entirely attribute this finding to our therapy with silymarin, curcumin, and garlic, a healthy lifestyle combined with these supplements can help improve the state of NAFLD. Further studies with larger sample size and different doses are recommended.